Safety, Immunogenicity, and 1-Year Efficacy of Universal Cancer Peptide–Based Vaccine in Patients With Refractory Advanced Non–Small-Cell Lung Cancer: A Phase Ib/Phase IIa De-Escalation Study. Issue 2 (7th September 2022) - Adotévi, Olivier; Vernerey, Dewi; Jacoulet, Pascale; Meurisse, Aurélia; Laheurte, Caroline; Almotlak, Hamadi; Jacquin, Marion; Kaulek, Vincent; Boullerot, Laura; Malfroy, Marine; Orillard, Emeline; Eberst, Guillaume; et al.
Abstract : PURPOSE: Universal cancer peptide–based vaccine (UCPVax) is a therapeutic vaccine composed of two highly selected helper peptides to induce CD4+ T helper-1 response directed against telomerase. This phase Ib/IIa trial was designed to test the safety, immunogenicity, and efficacy of a three-dose schedule in patients with metastatic non–small-cell lung cancer (NSCLC). PATIENTS AND METHODS: Patients with refractory NSCLC were assigned to receive three vaccination doses of UCPVax (0.25 mg, 0.5 mg, and 1 mg) using a Bayesian-based phase Ib followed by phase IIa de-escalating design. The primary end points were dose-limiting toxicity and immune response after three first doses of vaccine. Secondary end points were overall survival (OS) and progression-free survival at 1 year. RESULTS: A total of 59 patients received UCPVax; 95% had three prior lines of systemic therapy. No dose-limiting toxicity was observed in 15 patients treated in phase Ib. The maximum tolerated dose was 1 mg. Fifty-one patients were eligible for phase IIa. The third and sixth dose of UCPVax induced specific CD4+ T helper 1 response in 56% and 87.2% of patients, respectively, with no difference between three dose levels. Twenty-one (39%) patients achieved disease control (stable disease, n = 20; complete response, n = 1). The 1-year OS was 34.1% (95% CI, 23.1 to 50.4), and the median OS was 9.7 months, with no significant difference between dose levels. The 1-year progression-free survival and the median OS were 17.2% (95% CI, 7.8 to 38.3) and 11.6 months (95% CI, 9.7 to 16.7) in immune responders ( P = .015) and 4.5% (95% CI, 0.7 to 30.8) and 5.6 months (95% CI, 2.5 to 10) in nonresponders ( P = .005), respectively. CONCLUSION: UCPVax was highly immunogenic and safe and provide interesting 1-year OS rate in heavily pretreated advanced NSCLC.